Cooling Process of White Dwarf Stars in Palatini f(R) Gravity - Surajit Kalita; Lupamudra Sarmah; Aneta Wojnar (Universe, 2022)
A simple cooling model of white dwarf stars is re-analyzed in Palatini <semantics>f(R)</semantics> gravity. Modified gravity affects the white dwarf structures and consequently their ages. We find that the resulting super-Chandrasekhar white dwarfs need more time to cool down than sub-Chandrasekhar ones, or when compared to the Newtonian models.